2017
DOI: 10.3389/fphys.2017.01034
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Training Methods: Effects of Combining Resisted Sprints or Plyometrics with Optimum Power Loads on Sprint and Agility Performance in Professional Soccer Players

Abstract: The aim of this study was to compare the effects of two different mixed training programs (optimum power load [OPL] + resisted sprints [RS] and OPL + vertical/horizontal plyometrics [PL]) on neuromuscular performance of elite soccer players during a short-term training preseason. Eighteen male professional soccer players took part in this study. The athletes were pair-matched in two training groups: OPL + RS and OPL + PL. Unloaded and resisted sprinting speeds at 5-, 10-, 20-, and 30-m, change of direction (CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 44 publications
6
67
4
1
Order By: Relevance
“…Conversely, after the control period, we did not detect any worthwhile increases in the assessed variables. These results are similar to those previously described in team sport athletes [ 2 , 25 , 26 ]. To our knowledge, this is the first study to report these benefits in Olympic athletes from the individual sport of boxing.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, after the control period, we did not detect any worthwhile increases in the assessed variables. These results are similar to those previously described in team sport athletes [ 2 , 25 , 26 ]. To our knowledge, this is the first study to report these benefits in Olympic athletes from the individual sport of boxing.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, Kale et al [ 15 ] demonstrated that, among several variables collected in vertical and horizontal jumps, the drop jump height is the best indicator of maximum velocity attained by an elite sprinter throughout a 100-m dash race. Similar results were obtained in a series of recent investigations executed with sprinters and team sport athletes, confirming that the direction of the resistance force vector relative to the body is determinant in mediating adaptations to speed qualities [ 4 , 16 , 17 ]. However, although some of these studies have been carried out using vertical exercises performed at the optimum power zones (i.e., using loads capable of maximizing power output) [ 4 , 16 , 18 ], there is a lack of research on this topic with horizontally-directed exercises (e.g., hip-thrust).…”
Section: Introductionsupporting
confidence: 85%
“…this manipulation will impact on the number of times that players should apply force horizontally into the ground to overcome the inertia and move their bodies forward as rapidly as possible throughout a given workout. recent studies have shown that the development of training strategies (e.g., horizontally-directed exercises) which prioritize the application of force in the horizontal direction are paramount to significantly improve sprinting speed [45][46][47]. the present study found that the 40-m shuttle-sprint speed was very likely (99% chances of a real effect) improved after SrIt-3, but unclear changes (64/28/08%; ES = 0.33) were noticed following the SrIt-1 training model.…”
Section: Discussionmentioning
confidence: 99%